Competitiveness of Indonesia's Agricultural Exports To China: Trends and Strategic Insights - Novianti, Tanti; Sari, Anggi Mayang; Sari, Linda Karlina; Asikin, Zenal (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Economic development in open economies like Indonesia was marked by international trade. Starting with the restoration of diplomatic relations in 1990, China emerged as one of the biggest trading partners for Indonesia. However, Indonesia's competitiveness in the international market remained at a concerning level compared to other major exporters.Purpose: The research was conducted on the competitiveness of Indonesia's agriculture exports to China during 2019-2023, for certain commodities, and described Indonesia's current market position and growth prospects.Design/Methodology/Approach: The paper applied the Revealed Comparative Advantage and the methodologies of Export Product Dynamics in order to judge Indonesia's competitive position in major agricultural products, such as coconut, cashew nut, Brazil nut, coffee, nutmeg, cardamom, palm oil, copra, and natural rubber.Findings/Result: The analysis showed that nutmeg and cardamom showed outstanding growth, placing them in the